Influencia De La Depresión En Las Reservas Proteico-Energéticas Y El Índice De Masa Corporal En Adultos Mayores De 65 Años - Catherine Alexandra Andrade Trujillo; Dennys Leonardo Abril Merizalde (European Scientific Journal, ESJ, 2018)
The aim of the study was to analyze the influence of depression on the protein-energy reserves and the BodyMass Index in ederly. A total of 65 older adults were evaluated; to identify the level of depression, the Yesavage Geriatric Depression Scale was used, the protein-energy reserves were evaluated from the arm circumference and the Body Mass Index. The elderly with higher levels of depression had lower arm circumference than those who did not show depression according to the scale (p = 0.002 and p = 0.009, men and women respectively), a similar situation occurs with the BMI (p = 0.050 and p = 0.019). There is also a significant negative relationship between the Geriatric Depression Scale with the arm circumference and the BMI in women (r = -0.520, p = 0.002 and r = -0.439, p = 0.009 respectively). In men, this negative relationship is observed only between the Geriatric Depression Scale and the arm circumference (r = -0.479, p = 0.007). Older adults with a higher level of depression have lower arm circumference and lower BMI than those without depression. In both sexes, there is a significant negative relationship between the Geriatric Depression Scale score and the arm circumference. In females, an inversely proportional relationship between the scale and the Body Mass Index is evidenced.